Objectivity in Law Enforcement by Indonesia’s Civil Service Police Unit in Maintaining Public Order - Rio Winata; Dwi Afni Maileni; Rizki Tri Anugrah Bhakti (Siber Journal of Advanced Multidisciplinary, 2026)
Selective public-order enforcement in Indonesia continues to erode public trust and generate recurrent allegations of discriminatory practice. This article clarifies the legal meaning of ‘objectivity’ in enforcement by the Civil Service Police Unit (Satuan Polisi Pamong Praja, Satpol PP) and proposes an operational framework for assessing whether non-judicial public-order measures comply with the requirements of administrative justice. Using doctrinal legal research and statutory and conceptual approaches, the study examines the normative framework governing Satpol PP’s authority and standards of conduct. Particular attention is given to the multi-layered mandate derived from the 1945 Constitution, Law No. 23 of 2014, Government Regulation No. 16 of 2018, Law No. 30 of 2014 on Government Administration, and the General Principles of Good Governance (AUPB). The findings show that objectivity is not merely an ethical aspiration; it is a binding administrative standard that must be demonstrated through verifiable procedures and reasons. The study formulates eight interlocking parameters that translate this mandate into auditable practice: (1) a clear legal basis; (2) consistent enforcement criteria; (3) non-discrimination; (4) verified and documented facts; (5) proportional escalation; (6) minimum transparency through the provision of reasons; (7) traceable command accountability; and (8) accessible channels for objection and internal review. Together, these parameters provide a practical framework for designing, supervising, and auditing standard operating procedures and for distinguishing lawful, accountable enforcement from selective or abusive action, thereby strengthening the legitimacy of local public-order governance.